Paleogene and Late Cretaceous Pteropoda (Mollusca, Gastropoda, Heterobranchia) from North America - Garvie, Christopher L.; Goedert, James L.; Janssen, Arie W. (Zootaxa, 2020)
A comprehensive discussion and survey is made of all North American Paleogene and Late Cretaceous pteropods, and their systematics reviewed. From the West Coast of North America pteropod fossils have been collected from 23 localities in Washington State, and from the Gulf Coastal Plain they have been found in 40 localities. We also review earlier published specimens from boreholes in the Atlantic Coastal Plain. As a result, six new species are introduced from the Gulf Coast (Currylimacina asperita Garvie sp. nov., Heliconoides hodgkinsoni Garvie sp. nov., Limacina texanopsis Garvie sp. nov., Limacina parvabrazensis Garvie & Janssen sp. nov., Limacina pseudopygmaea Garvie & Janssen sp. nov., Cheilospicata cedrus Garvie sp. nov.) and one from Washington State (Clio gailae Goedert & Janssen sp. nov.). The geographical distribution and/or stratigraphic ranges of several species has been extended, for example, Limacina canadaensis Hodgkinson, 1992, is reported for the first time from western North America. Some species originally described from elsewhere, Altaspiratella multispira (Curry, 1982), Heliconoides bartonensis (Curry, 1965), L. karasawai Ando, 2011, L. aff. valvatina (Reuss, 1867), Creseis spina (Reuss, 1867) and Clio chadumica Korobkov, 1966, are reported for the first time from the Americas. New specimens of several poorly known species yielded additional information on morphology or biostratigraphy. It is shown that some species have longer temporal ranges in America, occurring in, or continuing into younger deposits than those in Europe. In addition to the only Cretaceous pteropod from Washington State known so far, several enigmatic species possibly representing Pteropoda are described from the Late Cretaceous (Maastrichtian) and Danian of Texas, which allows a salient discussion on the early history of Pteropoda. An enigmatic specimen from the Eocene of Texas might represent a very early form of Gymnosomata. This analysis shows that there may be more pteropod species represented during the Late Cretaceous and Paleocene than previously suspected.